Improving nutritional status and health outcomes in school-going adolescents: a randomized controlled trial of nutrition and WASH education interventions in Gojra, Pakistan - Perveen, Shagufta; Karmaliani, Rozina; Mistry, Rozina Farhad; Barolia, Rubina (Frontiers in Public Health, 2025)
The presence of both undernutrition and over-nutrition within a population is termed the double burden of malnutrition. Among school-going adolescents, prevalent micronutrient deficiencies are iron, iodine, vitamin A, and zinc. This study examined the effect of a school-based nutrition and WASH (Water, Sanitation and Hygiene) education on low body mass index (BMI;<18.5 kg/m2) and malnutrition symptoms among adolescents in Gojra. A randomized controlled trial was conducted involving 603 participants from grades 6 to 8, with 321 in the intervention group and 282 in the control group. Pre- and post-intervention assessments included validated questionnaire. Blood tests, anthropometric measurements, BMI evaluations and clinical assessments were performed to identify biochemical markers and cases of malnutrition. Following the intervention, a slight decrease in average BMI was observed (from 16.7 to 16.2 in boys and 18.5 to 17.6 in girls). Stunting increased in the control group but remained stable among intervention group of boys and showed only a slight rise in girls. Clinical improvement was noted in indicators such as hair, nails, eyes, and teeth, although biomarkers remained largely unchanged. In conclusion, the school-based intervention had a positive effect on clinical nutritional indicators and helped prevent further deterioration of nutritional status. While BMI and biomarkers showed minimal changes, the visible health improvements highlight the potential of integrated school health program to address the dual burden of malnutrition in adolescents.